Gender stereotypes in Nigerian films: a discursive analysis (2014)
Gender stereotypes influence people’s expectations and evaluations of what is appropriate for them and others. Gender stereotypes tend to exaggerate perceived differences of members of different groups and the perceived similarities of a particular man or woman to the general categories of male and female, which, in a way, can have a large effect on the way both sexes see themselves and how they are perceived in social relations. Studies have shown that the Nigerian film industry has the capacity to provide a platform for the positive promotion of Nigerian values. This paper examined the patterns of stereotypes being reinforced in Nigerian films and how these patterns affect the image of Nigerian women. It suggests that adequate information on gender issues such as abrogation of discriminatory customs, empowerment for low income women and men, reorientation of male chauvinism can be possible by using the platform of films to change gender stereotyping of women and projecting their positive images in Nigeria.